2021
DOI: 10.1002/jmor.21349
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and evolution of bioluminescent organs in the slimeheads (Teleostei: Trachichthyidae)

Abstract: Bacterial bioluminescent organs in fishes have a diverse range of tissues of origin, patterns of compartmentalization, and associated light‐conducting structures. The morphology of the perianal, bacterial bioluminescent organ of Aulotrachichthys prosthemius was described previously, but the light organ in other species of slimeheads, family Trachichthyidae, is poorly known. Here, we describe the anatomy of the bioluminescent organs in trachichthyids and places the evolution of this light‐producing system in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…The monophyly of Trachichthyiformes is supported in morphological (Zehren 1979;Moore 1993b;Baldwin and Johnson 1995;Konishi and Okiyama 1997) and molecular phylogenetic studies (Miya et al 2003(Miya et al , 2005; T. Grande et al 2013;Near et al 2013;Davis et al 2016;Betancur-R et al 2017;Dornburg et al 2017;Malmstrøm et al 2017;Musilova et al 2019;Ghedotti et al 2021;Ghezelayagh et al 2022;Mu et al 2022). Phylogenetic relationships among lineages of Trachichthyiformes inferred from morphological and molecular data differ substantially.…”
Section: Compositionmentioning
confidence: 99%
“…The monophyly of Trachichthyiformes is supported in morphological (Zehren 1979;Moore 1993b;Baldwin and Johnson 1995;Konishi and Okiyama 1997) and molecular phylogenetic studies (Miya et al 2003(Miya et al , 2005; T. Grande et al 2013;Near et al 2013;Davis et al 2016;Betancur-R et al 2017;Dornburg et al 2017;Malmstrøm et al 2017;Musilova et al 2019;Ghedotti et al 2021;Ghezelayagh et al 2022;Mu et al 2022). Phylogenetic relationships among lineages of Trachichthyiformes inferred from morphological and molecular data differ substantially.…”
Section: Compositionmentioning
confidence: 99%
“…Although Aulotrachichthys was initially established as a subgenus of Paratrachichthys by Fowler (1938), Gomon & Kuiter (1987) elevated it to a valid genus due to the presence of striated areas, a character shared with Sorosicthys but not Paratrachichthys . A recent phylogenetic and anatomic study conducted by Ghedotti et al (2021) showed that although not well-supported, Aulotrachichthys formed a monophyletic clade and is a sister clade with Sorosichthys and together formed a sister clade of Paratrachichthys . Moreover, they found that the structure of the light organ is different between Aulotrachichthys and Paratrachichthys .…”
Section: Introductionmentioning
confidence: 97%
“…Aulotrachichthys is characterized by having a rather slender body, body height at dorsal-fin origin < 40% standard length; its anus situated between pelvic-fin bases, and with a perianal bacterial bioluminescent organ; its body with a pair of silvery striated areas (tissue) along ventral-lateral side (Fig. 1); cycloid scales present between lateral line and pectoral-fin base; three to eight dorsal-fin spines; and six pelvic-fin soft rays (Gomon & Kuiter 1987, Kotlyar 1996, Ghedotti et al 2021, Matsunuma et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recognized four subgenera of Hoplostethus, i.e., Aulohoplostethus, Hoplostethus, Leiogaster and Macrohoplostethus, by the body colour, numbers of vertebrates, pyloric caeca and pectoral-fin rays, and size of abdominal scutes. Nonetheless, a recent phylogenetic study of Trachichthyoidei proposed by Ghedotti et al (2021) showed the polyphyly under Leiogaster and Hoplostethus. based his review and previous studies mostly on Russian material collected widely in the major oceans, including the southeastern Asian region around Japan and Taiwan, but did not report species specifically from Taiwanese waters.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a recent phylogenetic study of Trachichthyoidei proposed by Ghedotti et al . (2021) showed the polyphyly under Leiogaster and Hoplostethus .…”
Section: Introductionmentioning
confidence: 99%